2021
DOI: 10.1002/asia.202100904
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Water‐Soluble ZnXCd1‐XS Quantum Dot Photocatalyst at Room Temperature Assisted by 3‐Mercaptopropionic Acid

Abstract: An effective path to synthesize Zn x Cd 1-x S quantum dots (ZCS QDs) in aqueous phase at room temperature has remained relatively unexplored. Here, we developed a room-temperature, aqueous-phase approach to ZCS QDs, using 3-mercaptopropionic acid (MPA) to adjust the pH of the reaction precursor solution to regulate the competition between sulfur source and hydroxyl group, and realize the large-scale preparation of water-soluble ZCS QDs photocatalyst at room temperature. Without recombination with other materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Our previous work has shown that mass production can be achieved by this method. 25 Here, a new photocatalytic degradation approach for organic dyes is used, which is to directly prepare AgInS 2 QDs in organic dyes. This method can simulate the actual treatment of organic dyes in water directly in the raw material and the formation of QDs in water and can begin the photocatalytic degradation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work has shown that mass production can be achieved by this method. 25 Here, a new photocatalytic degradation approach for organic dyes is used, which is to directly prepare AgInS 2 QDs in organic dyes. This method can simulate the actual treatment of organic dyes in water directly in the raw material and the formation of QDs in water and can begin the photocatalytic degradation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we prepared a water-soluble Zn−Cd−S (ZCS) QD photocatalyst at room temperature with the assistance of 3-mercaptopropionic acid and described the nucleation mechanism of ZCS QDs. 25 The photocatalytic degradation of rhodamine B (RhB) can reach 98% within 1 min, showing high photocatalytic activity. Although ZCS nanocrystals (NCs) have high catalytic activity, many research groups are looking for suitable alternative materials because of the toxicity of Cd.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li et al developed an aqueous-phase approach to fabricate Zn x Cd 1Àx S QDs at room temperature, which greatly simplified the synthesis process. [35] Gao et al developed water-soluble Zn x Cd 1Àx S QDs and achieved a higher PHE rate than those of other Zn x Cd 1Àx S QDs fabricated by the conventional coprecipitation method, demonstrating the importance of using oil-and water-soluble Zn x Cd 1Àx S QDs for PHE. [36] Zhang et al reported hollow nanospheres of a Zn 0.46 Cd 0.54 S DS (DS-Zn 0.46 Cd 0.54 S) synthesized by a facile hydrothermal process.…”
Section: Morphology and Structure Engineeringmentioning
confidence: 99%
“…According to our previous reports, the feasibility of synthesizing ZCS QDs at room temperature has been confirmed. [12] However, in view of the fact that ZCS QDs cannot degrade organic dyes under visible light, this paper intends to enlarge the size of nanomaterials, improve the active sites on the crystal surface by adjusting the surface topography of materials, and change its photocatalytic ability under visible light. L-cysteine as sulfur source, can be prepared with different morphology and crystal structure (wurtzite, zinc blende/ wurtzite (Z/W) phase junctions, twin crystal) of ZnÀ CdÀ S solid solution.…”
Section: Introductionmentioning
confidence: 99%